Zygotic gene activation in mice: profile and regulation - AOKI, Fugaku (Journal of Reproduction and Development, 2022)
The zygotic genome is transcriptionally silent immediately after fertilization. In mice, initial activation of the zygotic genome occurs in the middle of the one-cell stage. At the mid-to-late two-cell stage, a burst of gene activation occurs after the second round of DNA replication, and the profile of transcribed genes changes dramatically. These two phases of gene activation are called minor and major zygotic gene activation (ZGA), respectively. As they mark the beginning of the gene expression program, it is important to elucidate gene expression regulation during these stages. This article reviews the outcomes of studies that have clarified the profiles and regulatory mechanisms of ZGA.